Idoso institucionalizado e a compreensão do seu cotidiano - Bessa, Maria Eliana Peixoto (2007)
When entering a rest home, many elders face one of its main features: the totalitarian nature of these institutions. Thus, it is necessary for them to adapt themselves to a new routine full of rules. Now they need, after spending their whole life living with people to whom they’ve had blood relation and friendship ties, to learn to live with completely unknown people, leaving their own lifestyle behind and not living their everyday lives anymore. This study has as its main aim: to understand how the elderly (re)build their everyday lives in a rest home, and as specific aims: 1) Know the reasons that took the elders to the rest home; 2) Investigate the process of adaptation to this new context; 3) Elucidate how the elders see themselves and how they organize their everyday life; and 4) Analyze the dynamics of the interpersonal relationships among the seniors in the rest home. This study was based on Callista Roy’s Adaptation Model theory of the adaptive process. The methodology chosen was the Case Study, since the research involved the natural universe of elder women living in a rest home, and had a comprehensive approach. The study happened in a philanthropic rest home in the city of Fortaleza-Ce, maintained by a religious order. The selected institution houses around 60 elders, all women. The sample was made selected resulting 9 elderly women at the end. The analytical component of this research was the (re)building of elderly women’s everyday life in the selected rest home. Case study was chosen in order to increase research reliability. Data was collected using both observations and interviews based on their life record. The observation was written in a diary and the interviews were recorded with a digital audio recorder, which were wholly transcribed, encoded, and analysed. For data organization and analysis, Discourse Analysis technique was used, which aims to understand how a symbolic element produces meanings, and how it is full of meanings to and for someone. This study was submitted and approved by the Ethics in Research Committee of the Hospital Complex at UFC. The categories, after the meanings in the speech were analysed, were: 1) Going to the rest home – main reasons: favoring religious practice, avoiding loneliness, other people’s influence, access to health care and family exclusion; 2) Adaptive process: feeling productive, feeling of losing/facing reality and previous knowledge of the rest home; 3) Self-awareness of the seniors in the rest home context: taking part and autonomy, and satisfaction and dissatisfaction of human needs; and 5) Relationships dynamics: respect. Through this study, it is realized that the (re)building of the elderly’s everyday life inside the rest home context is a complex activity which requires efforts from both elderly themselves and from the rest home, thus, it is necessary to be attentive to the adaptive process and the elderly’s human needs.